Pengembangan Media Pop Up Book Berbasis Permainan Pada Pembelajaran Tematik di Sekolah Dasar - Febriani Febriani (Universitas Negeri Makassar, 2022)
This research aims to describe the stages, feasibility, and student responses to game-based pop up book media in thematic learning in elementary schools. This study uses the research and development (R&D) method by Borg and Gall in Sukmadinata (2010: 169-170) which occurs from several stages as follows: (1) Conducting preliminary studies (2) Product planning (3) Product draft development (4 ) Individual trials (5) Revising the results of field trials (6) Limited trials, (7) Improvement of products resulting from limited trials (8) Extensive implementation tests (9) Completion of the final product. Data collection techniques were carried out using interview techniques, questionnaires and documentation. The research was conducted with 4 stages of validation, namely material expert validation, media expert validation, linguistic expert validation and student response questionnaires. The results showed that the validity level of material experts reached a percentage of 88% which was included in the